In silico screening of pomegranate (Punica granatum) and celery (Apium graveolens) metabolites for potential anti-type 2 diabetes activity - Auli, Winni Nur; Aziz, Syaikhul; Karim, Dewi Damayanti Abdul; Evanggeulista, Arnanda; Jannah, Aryn Fatkhul; Mendrofa, Alexander Yoel Harazachi (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2023)
Background: Alpha (α)-amylase is a popular pharmacological target for controlling postprandial blood glucose levels. The exploration of natural ingredients for drug development is particularly promising. Notably, pomegranate (Punica granatum) and celery (Apium graveolens) are rich in phenols and flavonoids, making them potential candidates for anti-type 2 diabetes treatments. Objective: This study aims to identify the most promising derivatives from pomegranate and celery using a combined metabolomic and in silico approach. Methods: The study began by identifying metabolites from the KnapSack database, selecting based on primary and secondary metabolites also selecting them based on their pharmacokinetic profile. The selected metabolites were then docked with alpha-amylase (PDB ID: 2QV4). Furthermore, the interactions were analyzed using Discovery Studio, and toxicity profiles were assessed in silico using ECOSAR and Toxtree software. Results: The analysis identified punicaflavone and 2-deoxybrassinolide as the compounds with the highest binding affinity, at -10.06 kcal/mol and -10.89 kcal/mol respectively, both surpassing acarbose’s -9.33 kcal/mol. These compounds interacted with 11 common residues in alpha-amylase, mirroring acarbose’s interactions. In silico toxicity analysis revealed that punicaflavone might pose risks to aquatic organisms but does not exhibit potential as a genotoxic or non-genotoxic carcinogen. Conversely, 2-deoxybrassinolide displayed moderate toxicity to aquatic organisms but was also free from genotoxic and non-genotoxic carcinogenic potential. Conclusion: Punicaflavone and 2-deoxybrassinolide emerged as the most promising compounds, demonstrating strong binding affinities and similar interaction patterns with α-amylase as acarbose. Although both compounds may pose risks to aquatic environments, they do not show potential as genotoxic or non-genotoxic carcinogens, supporting their further exploration as anti-diabetic agents.